Cover Picture: Heterogeneity of Graphite Lithiation in State‐of‐the‐Art Cylinder‐Type Li‐Ion Cells (Batteries & Supercaps 2/2021). Issue 2 (18th January 2021) - Petz, Dominik; Mühlbauer, Martin J.; Schökel, Alexander; Achterhold, Klaus; Pfeiffer, Franz; Pirling, Thilo; Hofmann, Michael; Senyshyn, Anatoliy
Abstract : The Front Cover displays the lithium distribution in the graphite anode of 18650‐type Li−ion battery. A look into the cell's interior illustrates a non‐destructive character of the performed studies. The background template corresponds to the structure of lithiated graphite, referring to the diffraction technique as a tool for spatially resolved quantification of lithium concentration in the cell. More information can be found in the Article by A. Senyshyn and co‐workers .